Anti-angiogenic therapy in head and neck squamous cell carcinoma - current limitations and future directions - Nieberle, Felix; Spoerl, Steffen; Głuszko, Alicja; Taxis, Juergen; Spanier, Gerrit; Erber, Ramona; Spörl, Silvia; Szczepański, Mirosław J.; Beckhove, Philipp; Reichert, Torsten E.; Whiteside, Theresa L.; Ludwig, Nils (Vessel Plus, 2024)
Angiogenesis, the formation of new blood vessels, plays a crucial role in the progression and metastasis of various cancers, including head and neck squamous cell carcinoma (HNSCC). HNSCCs are characterized by altered levels of angiogenesis-related factors, including the overexpression of pro-angiogenic factors such as vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF), as well as the dysregulation of angiogenesis inhibitors. Together, these factors drive the formation of new blood vessels within the tumor microenvironment and are considered therapeutic targets in HNSCC. Although preclinical studies are promising, challenges have emerged in the clinical use of anti-angiogenic agents in the clinic, including treatment-related toxicities and the development of resistance to therapy. There is an unmet need for further research to elucidate the molecular pathways involved in HNSCC angiogenesis, identify novel therapeutic targets, and discover predictive biomarkers to improve patient selection.
CRIS-Team Scopus Importer:2024-07-19
Keywords: antiangiogenic therapy; Head and neck squamous cell carcinoma; HNSCC; oral squamous cell carcinoma; OSCC; tumor angiogenesis